Developing an English Grammar Practice Book based on Multicultural Values for Second-year University Students - Andianto andianto; Leny Setyana; Eka Yuniasih; Restina Damayanti (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2021)
The aim of this study is to develop an English grammar practice book model based on multicultural values as teaching materials for compulsory subjects of the university in Indonesia. This research-based on Research and Development approach, which is adopted from Gall, Gall, and Borg (2003). The data were collected through interviews and questionnaires. While qualitative data were analyzed using an interactive analysis and quantitative data analysis used percentages. The research participants consisted of lecturers and students at two universities in Indonesia. The findings showed that 1) the conceptual model of the English grammar practice book is applicable and contextual which presents the latest issues in accordance with the issue of Indonesian multicultural values. 2) The content of an English grammar practice book constitutes the following components: chapter titles, introductions, material presentation and elaboration of multicultural values, competence performances, summaries, reflections, variation exercise. It is suggested that the textbook model more help in developing multicultural competencies students in communication with other people from different backgrounds through using English as an international language.